6 fj vfjaoc; fj VOCTTOS (The Best of the Argonauts, 1993)
Colorectal cancer (CRC) remains a leading cause of cancer mortality globally, with therapeutic efficacy hindered by tumor heterogeneity and drug resistance. While organoid technology offers unprecedented opportunities to model tumor complexity, systematic platforms for chemo-targeted combination screening and molecular mechanisms underlying chemoresistance remain underexplored in Chinese populations. Here, we established a biobank of 17 patient-derived CRC organoids (85% success rate) from treatment-naïve surgical specimens, preserving histopathological fidelity and molecular diversity of parental tumors. High-throughput drug screening across eight clinical regimens revealed different responses. To dissect chemoresistance mechanisms, six organoids representing extreme phenotypes (three sensitive and three resistant, based on IC50 difference for irinotecan + raltitrexed) were selected from this cohort for single-cell transcriptomic analysis. Single-cell transcriptomics of irinotecan + raltitrexed-treated organoids identified chemoresistance-associated clonal expansion of epithelial subpopulations (cluster_0), characterized by overexpression of REG4/TFF1/TFF3 and epithelial keratins (KRT19/KRT8/KRT18). Intercellular network analysis revealed intra-epithelial communication as a resistance hub, mediated by 32 ligand-receptor pairs. Integration with TCGA-COAD cohort (n = 378) demonstrated intratumoral heterogeneity (ITH) score as an independent prognostic determinant, outperforming stemness/angiogenesis metrics. Machine learning consensus identified CEACAM6 and KRT19 as dual regulators of mortality and ITH through epithelial plasticity networks. Our multi-omics framework establishes organoid-guided chemoresistance mechanisms while proposing ITH quantification targeting as precision strategies. This study bridges critical gaps in CRC therapeutic personalization, offering clinically actionable insights for overcoming treatment failure.